Peran Digital Marketing dalam Upaya Peningkatan Omset Penjualan di Era Pandemi Covid-19 (Studi Kasus : UKM Deva Bag Desa Jiken Kecamatan Tulangan Kabupaten Sidoarjo) - Isnainiyah, Fauziatul; Naily, Nabiela; Muttaqim, Zainal (VIVABIO: Jurnal Pengabdian Multidisiplin, 2021)
WHO states that the Covid-19 virus is a pandemic, so the Indonesian government has implemented various policies to break the chain of spread of COVID-19. The prohibition of gathering or gathering is one of them, so everything must be done online and done at home. This pandemic has had a very bad impact on economic sustainability, many people have experienced a decline in income due to the Covid-19 pandemic, and many have even lost their jobs. One of the economic sectors that is feeling the impact of the pandemic is Small and Medium Enterprises (SMEs). The Deva Bag SMEs is no exception in Jiken Village, Tulangan District, Sidoarjo Regency. With the current pandemic conditions, of course, SMEs must survive so an alternative marketing strategy is needed. Therefore, strategies such as digital marketing are needed which include sales through social media to marketplaces in an effort to increase SME turnover. So this research was conducted with the aim of providing education about digital marketing to Deva Bag SMEs in Jiken Village, Tulangan Regency. The method used is interviews and action research in the form of counseling and education about digital marketing. The activity was carried out properly and regularly, Deva Bag SMEs Desa Jiken was very enthusiastic about wanting to know more about the digital marketing system/strategy.